2015
DOI: 10.4269/ajtmh.14-0644
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Tests for the Detection of Schistosoma mansoni Infection in Children in Western Kenya

Abstract: Abstract. Financial resources tend to be limited in schistosomiasis endemic areas, forcing program managers to balance financial and scientific considerations when selecting detection assays. Therefore, we compared the costs of using single stool Kato-Katz, triplicate stool Kato-Katz, and point-of-contact circulating cathodic antigen (POC-CCA) assays for the detection of Schistosoma mansoni infection. Economic and financial costs were estimated from the viewpoint of a schistosomiasis control program using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…For example, our data suggest that although individuals with 2+ and 3+ results would be clearly positive, perhaps only a proportion of the 1+ results should be counted toward the prevalence of infected persons in a given school or village. Despite concerns about the cost of the POC-CAA cassettes in comparison to Kato-Katz supplies, similar to Adriko and others, 17 we found that when equipment, labor, and transportation expenses are included, the costs of performing prevalence mapping using POC-CCA are comparable to those for Kato-Katz (Worrell and others 32 ). In addition, bulk production and purchasing of the cassettes, particularly in the context of drug administration programs, have real potential for cost savings.…”
Section: Discussionsupporting
confidence: 72%
“…For example, our data suggest that although individuals with 2+ and 3+ results would be clearly positive, perhaps only a proportion of the 1+ results should be counted toward the prevalence of infected persons in a given school or village. Despite concerns about the cost of the POC-CAA cassettes in comparison to Kato-Katz supplies, similar to Adriko and others, 17 we found that when equipment, labor, and transportation expenses are included, the costs of performing prevalence mapping using POC-CCA are comparable to those for Kato-Katz (Worrell and others 32 ). In addition, bulk production and purchasing of the cassettes, particularly in the context of drug administration programs, have real potential for cost savings.…”
Section: Discussionsupporting
confidence: 72%
“…This agrees with Worrell et al . who stated that when the prevalence of schistosomiasis in an area is less than 50% by KK thick smear, POC‐CCA will show higher prevalence rates; reaching even double that recorded by KK. Ochodo et al .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, any cost-savings resulting from the use of more rapid tests will be very sensitive to the increase in number of schools/survey sites that can be sampled per day (highlighted by the different curves in Figure 1 and [18]), and therefore dependent on the population density of the survey area. Furthermore, the relative costs of different tests will also vary depending on the sample size (as the amount of economies of scale relating to different tests may not be the same (Figure 1).…”
Section: Comparing the Costs And Cost-effectiveness Of New Methodsmentioning
confidence: 99%